Investment Risks in Commodity Futures Trading from a Sharia Economic Perspective - Muhammad Ariyanto; Tri Hidayati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Commodity Futures had become a rapidly growing investment instrument in Indonesia since the enactment of Law Number 10 of 2011. Data from the Commodity Futures Trading Regulatory Agency indicated a significant upward trend in trading volume, highlighted by a major surge in 2022 reaching 14.97 million lots. While offering substantial opportunities for investors through hedging functions and price discovery, futures trading also carries high risks due to market volatility and speculative tendencies. Accordingly, financial literacy particularly from a Sharia economic perspective plays a crucial role in strengthening public understanding of associated market risks. This article aims to analyze commodity futures trading within the framework of Islamic economics, emphasizing principles of justice, transparency, and the prohibition of riba (interest), gharar (uncertainty), and maysir (gambling). The National Sharia Council of the Indonesian Ulema Council (DSN-MUI) Fatwa No. 96/2015 on Sharia hedging serves as a key reference in assessing the conformity of PBK practices with Islamic law. This research employs a literature study method by reviewing relevant academic sources, regulations, and fatwas. The findings show that futures trading is permissible under Sharia principles as long as it supports real economic needs, ensures transparency, and remains free from harmful speculative practices. Thus, increasing Sharia-based financial literacy and risk comprehension is essential in encouraging prudent public participation while safeguarding Sharia compliance and supporting sustainable economic development.